Distribution Of Phenotypic And Genotypic Abo And Rhesus Blood Groups Among Bangladeshi Population - Dipta, Tashmim Farhana; Iqbal, Md Roushan; Hossain, Ahmed Zahid; Rahman, Md Tahminur; Chowdhury, Subhagata (Ibrahim Medical College Journal, 2012)
The present study is a retrospective analysis of allelic frequency of ABO and Rhesus (D) blood groups of donors attending the Deaprtment of Transfusion Medicine of Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorders (BIRDEM), Dhaka. BIRDEM IS a 625 bed hospital, where patients and blood donors come from all parts of Bangladesh. A total of 1, 28,506 blood donors of both genders were included in the study over fourteen years from June 1995 to June 2009 for analysis. Blood group was determined by performing the both tube and slide method blood grouping method. The distribution of blood groups in our population was B>O>A>AB in Rh positive groups donors and O>B>A>AB among Rh negative donors. Blood group B was more common among the males (37.42%) while O was predominant among female donors (33.83 %). On the other hand, blood group O negative was predominant in both genders (36.88%). In this study, Hardy- Weinberg equilibrium law was used to calculate the allelic frequency for ABO/ Rh system. Homozygous allelic frequency for Rh negative population was only 0.0007. Although phenotypically B group was dominant and AB was rare in our population, but according to Hardy- Weinberg equilibrium law the estimated allelic frequency of A (0.3694) and O (0.3040) showed higher frequency than B type (0.2300) in Bangladeshi population in both homozygous and heterozygous state. So, with increasing population of Bangladesh, this changing trend in estimated blood group in ABO system may play an important role in our genetic pattern. DOI: http://dx.doi.org/10.3329/imcj.v5i2.10101 IMCJ 2011; 5(2): 59-62